Biomimetic three-dimensional anisotropic geometries by uniaxial stretch of poly(ɛ-caprolactone) films for mesenchymal stem cell proliferation, alignment, and myogenic differentiation - Wang, Zu-yong (2013)
Anisotropic geometries are critical for eliciting cell alignment to dictate tissue microarchitectures and biological functions. Current fabrication techniques are complex and utilize toxic solvents, hampering their applications for translational research. Here, we present a novel simple, solvent-free, and reproducible method via uniaxial stretching for incorporating anisotropic topographies on bioresorbable films with ambitions to realize stem cell alignment control. Uniaxial stretching of poly(ɛ-caprolactone) (PCL) films resulted in a three-dimensional micro-ridge/groove topography (inter-ridge-distance: 6 μm; ridge-length: 90 μm; ridge-depth: 200–900 nm) with uniform distribution and controllable orientation by the direction of stretch on the whole film surface. When stretch temperature (Ts) and draw ratio (DR) were increased, the inter-ridge-distance was reduced and ridge-length increased. Through modification of hydrolysis, increased surface hydrophilicity was achieved, while maintaining the morphology of PCL ridge/grooves. Upon seeding human mesenchymal stem cells (hMSCs) on uniaxial-stretched PCL (UX-PCL) films, aligned hMSC organization was obtained. Compared to unstretched films, hMSCs on UX-PCL had larger increase in cellular alignment (>85%) and elongation, without indication of cytotoxicity or reduction in cellular proliferation. This aligned hMSC organization was homogenous and stably maintained with controlled orientation along the ridges on the whole UX-PCL surface for over 2 weeks. Moreover, the hMSCs on UX-PCL had a higher level of myogenic genes' expression than that on the unstretched films. We conclude that uniaxial stretching has potential in patterning film topography with anisotropic structures. The UX-PCL in conjunction with hMSCs could be used as “basic units” to create tissue constructs with microscale control of cellular alignment and elongation for tissue engineering applications.